Vocalizing humpback whales (Megaptera novaeangliae) migrating from Antarctic feeding grounds arrive earlier and earlier in the Perth Canyon, Western Australia - Gosby, Corinna; Erbe, Christine; Harvey, Euan S.; Figueroa Landero, Marcela Montserrat; McCauley, Robert D. (Frontiers in Marine Science, 2022)
Migratory species undertake seasonal, long-distance travel between feeding and breeding grounds, and time their arrivals with high-quality resources. The Breeding Stock D population of humpback whales (Megaptera novaeangliae) migrates from Antarctic to Western Australian waters every austral winter. Based on 16 years (2002-2017) of passive acoustic recordings in the Perth Canyon, Western Australia, the hourly presence/absence of humpback whale vocalizations was used as an indicator of inter-annual changes in migration timing. A trend of earlier arrivals in the Perth Canyon by 1.4 days/year during the northward migration and possibly earlier departures from the Perth Canyon during the southward migration was observed. A distance-based linear model and a generalized linear model (GLM) both identified sea surface temperature (SST) as the most significant predictor for acoustic presence in the Perth Canyon. A 1 °C increase in SST corresponded to a decrease in humpback whale acoustic presence by 4.4 hours/day. Mean SST at the peak of the humpback whale season in the Perth Canyon was 19 °C. Exploratory analysis of the metocean environment of the Antarctic feeding grounds suggested that whales were leaving the Antarctic at the end of the austral summer, as sea ice concentration (SIC) increased and SST decreased. Further research should investigate whether changes in the metocean conditions on Australian breeding grounds correspond to changing departures from the Perth Canyon during the southward migration. If environmental conditions on breeding and feeding grounds change out-of-sync, migrating whales might be unable to arrive at either ground during optimal conditions.